CONTENT OF ASSESSMENT OF THE STUDENT'S COMPETENCES IN LEARNING THE GERMAN LANGUAGE (Academia Science Repository, 2023)
The article talks about the importance of test tasks in assessing the student's competencies in mastering the German language, and suggests the developmental purpose of the test. In this regard, specific suggestions are made and the essence of the issue is revealed.